Automatic delirium prediction system in a Korean surgical intensive care unit. Issue 6 (24th October 2013) - Oh, Suk‐Hwa; Park, Eun‐Ju; Jin, Yinji; Piao, Jinshi; Lee, Sun‐Mi
ABSTRACT Background In Korea, regular screening for delirium is not considered essential. In addition, delirium is often associated with vague concepts, making it harder to identify high‐risk patients and impeding decision‐making. Aims To assess the impact of the Automatic PREdiction of DELirium in Intensive Care Units (APREDEL‐ICU) system on nursing‐sensitive and patient outcomes for surgical ICU patients and to evaluate nurse satisfaction with the system and its usability. Methods A pre‐post research design was adopted. Our study included 724 patients admitted before the implementation of the APREDEL‐ICU (January to December 2010) and 1111 patients admitted after the system was installed (May 2011 to April 2012). The APREDEL‐ICU uses a pop‐up window message to inform the nursing staff of patients at risk for delirium, allowing evidence‐based nursing interventions to be applied to the identified patients. A total of 42 nurses were surveyed to determine the system's usability and their level of satisfaction with it. Results After the implementation of APREDEL‐ICU, high‐risk patients, determined using a prediction algorithm, showed a slight decrease in the incidence of delirium, but the changes were not significant. However, significant decreases in the number and duration of analgesic/narcotic therapies were observed after the implementation of the system. Nurse self‐evaluation results showed an improvement in all categories of knowledge regarding delirium care. Conclusion The use of a prediction and alerting system for ICU patients at high risk of delirium showed a potential increase in the quality of delirium care, including early detection and proper intervention.